A high-throughput screening assay for eukaryotic elongation factor 2 kinase inhibitors - Ting Xiao; Rui Liu; Christopher G. Proud; Ming-Wei Wang (Elsevier, 2016)
Eukaryotic elongation factor 2 kinase (eEF2K) inhibitors may aid in the development of new therapeutic agents to combat cancer. Purified human eEF2K was obtained from an Escherichia coli expression system and a luminescence-based high-throughput screening (HTS) assay was developed using MH-1 peptide as the substrate. The luminescent readouts correlated with the amount of adenosine triphosphate remaining in the kinase reaction. This method was applied to a large-scale screening campaign against a diverse compound library and subsequent confirmation studies. Nine initial hits showing inhibitory activities on eEF2K were identified from 56,000 synthetic compounds during the HTS campaign, of which, five were chosen to test their effects in cancer cell lines.